Durability performance of rubberised fibre mortar - Ahmad Musa, Mukaddas (2015)
High cost of building materials and reduction of healthy environmental conditions due to excessive use of natural aggregates had leads many researchers to find alternative replacement materials for construction. At the same time, abundance of recyclable nonbiodegradable solids such as waste tyres and oil palm fruit fibre (OPFF) cause crucial environmental problems if not disposed well. Hence this research is carried out to make used of those waste materials as replacement of natural aggregates and as addition to enhance the durability performance of rubberised fibre mortar (RFM). RFM is a mix combination of treated crumb rubber (TRC) and OPFF in producing a ‘greener’ lightweight mortar. The RFM mix composition is made of 10 to 30% TCR as sand replacement and addition of 1% to 1.5% OPFF producing sixteen different mixes, in which all mixture are using water to cement ratio of 0.48. The mechanical properties of these 16 RFM mixes are well studied earlier; however none are reported on the durability aspects. Durability is influenced by temperature, humidity and curing methods. This study focuses on two types of water curing called ponding and wetting which are practical for brick/block production, which is the potential application of the mixtures. The specimens were cured by each curing method for 28 days before being subjected to compressive strength, chloride ion penetration resistance, water permeability under hydrostatic pressure, water absorption, Sodium Sulphate ingress and carbonation depth tests. These tests were carried out to evaluate the durability performance of the mixes. Based on the results obtained, the durability performance of RFM has significantly influenced by addition of OPFF and replacement of TCR. It was discovered that RFM mix containing 1.0% OPFF and 30% TCR for both curing methods can adequately sustain CO2 penetration, moderate chloride ion penetration resistance and sulphate aggression. Medium permeability and moderate absorption characteristics were possible with RFM of 1% OPFF and 20% TRC for both curing methods. Density of RFM significantly decreased while structural lightweight concrete was achieved up to 30% TCR for both curing methods. There was insignificant effect of curing on sulphate and chloride ion penetration resistance of the RFM mixes. In conclusion it was found that RFM mix of 1.0% OPFF with any of 10% - 30% TCR replacements have potential applications in brick/block productions as it meets the durability requirements of lightweight materials.